PENGARUH MEDIA PERMAINAN ULAR TANGGA TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI - Erika Rahayu; Rusmin AR; Deskoni Deskoni (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2019)
The study aimed to prove the effect of snakes and ladders game media on the 11th grade students learning results in economic subject in State Senior High School 10 Palembang. This was experimental study that used Quasi Experimental Design in Post Test Only Control Design. The population of this study were all of the 11th grade social sciences students in State Senior High School 10 Palembang in the even semester of 2018/2019. The sampling technique used Cluster Random Sampling by drawing so it’s obtained third 11 th grade social sciences as experimental grade and fourth 11 th grade social sciences as control grade. The data werecollected by test and observation. The data analysis techniques on students learning results data were obtained from the post test and grouped into the Minimum Completion Criteria category and the data observation analyses were obtained from observer’s observations during the learning process. The hypothesis used parametric statistics with pearson product moment correlation, coefficient determination then t-test with the polled variance formula was conducted and it’s obtained tcounted (15,09) ≥ ttable (1,674) so Ha was accepted and Ho was rejected. It could be concluded that there was the effect of snakes and ladders game media on the 11th grade students learning results in economic subject in State Senior High School 10 Palembang.